Neurochemical organization of the ventral striatum's olfactory tubercle. Issue 4 (7th January 2020) - Cansler, Hillary L.; Wright, Katherine N.; Stetzik, Lucas A.; Wesson, Daniel W.
Abstract : Abstract: The ventral striatum is a collection of brain structures, including the nucleus accumbens, ventral pallidum and the olfactory tubercle (OT). While much attention has been devoted to the nucleus accumbens, a comprehensive understanding of the ventral striatum and its contributions to neurological diseases requires an appreciation for the complex neurochemical makeup of the ventral striatum's other components. This review summarizes the rich neurochemical composition of the OT, including the neurotransmitters, neuromodulators and hormones present. We also address the receptors and transporters involved in each system as well as their putative functional roles. Finally, we end with briefly reviewing select literature regarding neurochemical changes in the OT in the context of neurological disorders, specifically neurodegenerative disorders. By overviewing the vast literature on the neurochemical composition of the OT, this review will serve to aid future research into the neurobiology of the ventral striatum. Abstract : The olfactory tubercle is a structure within the ventral striatum that has received relatively little attention. In this review, we provide a detailed summary of the olfactory tubercle's rich neurochemistry, including the neurotransmitters present as well as their associated receptors, transporters and putative functions. In addition, we briefly review the literature pertaining to neurochemical changes in the olfactory tubercle in neurodegenerative disorders. This review will serve to aid future research into the olfactory tubercle and the ventral striatum as a whole. The figure is based in part upon (Xiong & Wesson, 2016) and was re‐drawn by Marco Bazelmans in BioRender (https://biorender.com/ ).